Estimating mean dynamic topography in boundary currents and the use of Argo trajectories. Issue 12 (11th December 2014) - Bowen, Melissa; Sutton, Philip; Roemmich, Dean
Abstract A Mean Dynamic Topography (MDT) is required to estimate mean transport in the ocean, to combine with altimetry to derive instantaneous geostrophic surface velocities, and to estimate transport from shipboard hydrography. A number of MDTs are now available globally but differ most markedly in boundary currents and the Antarctic Circumpolar Current. We evaluate several MDTs in two boundary currents off New Zealand (in the subtropical western boundary current system east of the country and in the Subantarctic Front to the south) using satellite, hydrographic, and Argo observations near two altimeter tracks. Argo float trajectories are combined with estimates of shear to produce new MDTs along both altimeter tracks: sufficiently high numbers of Argo floats travel in both boundary currents to allow a useful estimate of the mean flow at 1000 m depth and conservation of potential vorticity is used to account for more realistic flow paths. In finding a MDT, we show the uncertainties in the estimates of velocity differences between 1000 m and the surface from density climatologies, while often not estimated, need to be considered. The MDT computed from the Argo trajectories is generally consistent with the CLS09 MDT in both boundary currents and, in some locations, distinctly different from the MDT using a "level of no motion" assumption. The comparison suggests velocities from Argo trajectories can be usefully combined with other observations to improve estimates of flows and MDT in boundary currents.